2007
DOI: 10.3748/wjg.v13.i43.5736
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of major depression in chronic hepatitis C patients during peg-interferon α-2b treatment by assessment of vegetative-depressive symptoms after four weeks

Abstract: sensitivity at a cut-point of > 15/35 was 95% (95% CI: 74-100). The positive predictive value equalled 44% (95% CI: 29-60). CONCLUSION:In this group of Belgian CHC patients infected after substance use, antiviral treatment caused a considerable risk of depression. Seven vegetativedepressive symptoms of the Zung scale at wk 4 of treatment predicted 95% of all emerging depressions, at a price of 56% false positive test results. INTRODUCTIONFollowing the recent expert consensus, patients with chronic hepatitis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Robaeys et al116 found that vegetative-depressive symptoms at week 4 of treatment were predictive of a subsequent diagnosis of MDD; however, there were no differences between groups at baseline. Likewise, decreased motor speed was associated with increased symptoms of depression and fatigue 134…”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Robaeys et al116 found that vegetative-depressive symptoms at week 4 of treatment were predictive of a subsequent diagnosis of MDD; however, there were no differences between groups at baseline. Likewise, decreased motor speed was associated with increased symptoms of depression and fatigue 134…”
Section: Limitationsmentioning
confidence: 98%
“…However, it is not clear whether this observed dose effect also holds for the development of depression (see Table 4). In general, rates of depression in patients taking IFN-α for HCV vary from 0%109,118 to up to 50% 21,62,97,99101,104,108,113,116. Oncology patients taking up to five times the dose of IFN-α than those patients infected with HCV are prescribed have similar rates of depression from 5%119 up to 50% 120.…”
Section: Review Of Risk Factorsmentioning
confidence: 99%
“…Remarkably, individuals who respond with enhanced corticotropin-releasing hormone and p38 mitogen-activated protein kinase responses within 12 h of a first infusion or injection are significantly more likely to develop clinically relevant depressive symptoms 1 or 2 months later in the midst of IFN-α treatment [67•, 68]. On a symptomatic level, people who respond to a first dose with increased sickness-type symptoms are far more likely to meet full criteria for MDD (including profound emotional distress) by 8 weeks of IFN-α therapy [69, 70]. Also as shown in Fig.…”
Section: Do Inflammatory Processes Contribute To a Majority Or Only Amentioning
confidence: 99%
“…This consist of behavioural changes, including disturbance in sleep, appetite, psychomotor slowing, memory impairment and behaviour, that are thought to be very similar to biological symptoms of depression in humans 67 68. Interferon therapy is associated with sickness-like symptoms, including lack of sleep, loss of appetite, weight loss and fatigue, usually occurring during the first 2–4 weeks of therapy, that can be early indicators of depression which usually develops 1–3 months after treatment 69 70. Capuron et al found that in spite of considerable overlap in symptoms between cytokine induced depression and idiopathic depression in medically healthy subjects, psychomotor symptoms were much greater in the cytokine induced MDD group while cognitive distortions were greater in those with idiopathic MDD.…”
Section: How May Proinflammatory Cytokines Cause Mdd?mentioning
confidence: 99%